A Novel De Novo Pathogenic Variant in FOXF1 in a Newborn with Alveolar Capillary Dysplasia with Misalignment of Pulmonary Veins - Ma, Youngeun; Jang, Mi-Ae; Yoo, Hye Soo; Ahn, So Yoon; Sung, Se In; Chang, Yun Sil; Ki, Chang-Seok; Park, Won Soon (Yonsei medical journal, 2017)
Alveolar capillary dysplasia with misalignment of pulmonary veins (ACD/MPV) is an autosomal dominant, fatal developmental disorder of the lungs, with a mortality rate of about 100%. ACD/MPV is caused by mutations in FOXF1. Herein, we describe a newborn boy with ACD/MPV carrying a novel pathogenic variant of FOXF1. The patient developed respiratory distress and severe pulmonary hypertension on the first day of life. Despite aggressive cardiorespiratory management, including veno-venous extracorporeal membrane oxygenation, his condition deteriorated rapidly, and he died within the first month of his life. Lung histology showed the characteristic features of ACD/MPV at autopsy. Sequence analysis of FOXF1 from genomic DNA obtained from autopsied lung tissue revealed that the patient was heterozygous for a novel missense variant (c.305T>C; p.Leu102Pro). Further analysis of both parents confirmed the de novo occurrence of the variant. To the best of our knowledge, this is the first report of genetically confirmed ACD/MPV in Korea.